Pengaruh Customer Relationship Management Terhadap Kepuasan dan Loyalitas Nasabah PT Bank BNI - Nelli Purnama Sari; Heny K Daryanto; Imam Teguh Saptono (School of Business, Bogor Agricultural University (SB-IPB), 2018)
Banking businesses in Indonesia have grown very rapidly and they have to make efforts to survive. Banks have realized the need of a strategy in managing customer relationship to retain their customers for the businesses. Customer relationship management (CRM) is a strategy that is able help them to build long lasting relationships with their customers and increase profits. The objectives of this study were to identify the implementation of CRM and factors of CRM which have the most dominant influences on customer satisfaction and loyalty on Taplus of PT BNI (Persero) Tbk of the regional office of Jakarta BSD. The data were analyzed using the structural equation model (SEM). The survey results showed that 92.15% of the respondents stated that BNI WJB CRM performance level has been very good, while 7.85% of said the performance has been reasonably good. CRM indicators that have significant and dominant influences include the process and knowledge with a loading factor of 0.89. The results of the study showed that CRM variable significantly influences the customer satisfaction and customer loyalty; however, customer satisfaction insignificantly influences the customer loyalty.Keywords: customer relationship management, customer satisfaction, customer loyalty, SEM, BNI